HLA Class II (DRB, DQA1 and DQB1) Allele and Haplotype Frequencies in the Patients with Pemphigus Vulgaris - Shams, Sheida; Amirzargar, Ali Akbar; Yousefi, Maryam; Rezaei, Nima; Solgi, Ghasem; Khosravi, Farideh; Ansaripour, Bita; Moradi, Batoul; Nikbin, Behrouz (Journal of clinical immunology, 2009)
Introduction Pemphigus vulgaris (PV), an autoimmune disease affecting the skin and mucous membranes, is associated with some human leukocyte antigen (HLA) class II alleles and haplotypes. Materials and Methods In order to evaluate the association of HLA-DR and DQ alleles and haplotypes in Iranian non-Jewish patients with PV, 52 patients with PV and 180 normal subjects as control group were investigated in this study. Results and Discussion HLA-DRB1*04, -DRB1*1401, -DRB4, -DQA1*0104, -DQA1*03011, -DQB1*0302, and -DQB1*0502 alleles have been significantly increased in our patients group. Moreover, the haplotypes HLA-DRB1*04/-DQA1*03011/-DQB1*0302 and HLA-DRB1*1401/-DQA1*0104/-DQB1*0502 increased significantly in our patients. In contrast, the following alleles decreased significantly in our patients: HLA-DRB1*15, -DRB1*0301, -DRB1*07, -DRB1*11, -DRB5, -DQA1*0101, -DQA1*0103, -DQA1*201, -DQA1*05, -DQB1*0201, -DQB1*0301, -DQB1*06011, and -DQB1*0602. In addition, HLA-DRB1*15/-DQA1*0103/-DQB1*06011, HLA-DRB1*0301/-DQA1*05011/-DQB1*0201, HLA-DRB1*07/-DQA1*0201/-DQB1*0201, and HLA-DRB1*11/-DQA1*05/-DQB1*03011 decreased significantly in our patients. Genetic factors are involved in the occurrence of PV; HLA-DRB1*04 and -DRB1*1401 alleles and the related haplotypes are suggestive to be two major PV susceptibility factors in our population study.